Rights of nature, defense and warranty; legal and social analysis in communities of Azuay: Derechos de la naturaleza, defensa y garantías; análisis jurídico y social en comunidades del Azuay - Ramírez Álvarez, Fernanda Yadira; Verdugo, Teodoro; Cordero, Fabián; Gómez, Paola (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2024)
The study in seven communities in the province of Azuay in Ecuador, had goal determining the knowledge of populations of rights of nature, citizen participation, social control and if there are infringement of this, analyzed legally and socially the rights of participation in relationship with rights of Nature enforcement and guarantee, the rights of participation as an element necessary for effective compliance of rights of nature, through quantitative and qualitative analysis. The majority of population considers that they know about rights, four of the communities do not that these rights are enshrined in the Constitution, it is meaning that they do know, generate a limiting for reach the defense it. It found the necessity to educate for protect and defend the rights of nature, to know the rights, as a requirement of the defense for the appropriation of the norms and participation tools, as a citizen